Persepsi pemustaka terhadap sikap pustakawan dalam memberikan layanan sirkulasi di Unit Pelaksana Teknis (UPT) Perpustakaan Universitas Islam Negeri Sulthan Thaha Saifuddin Jambi jambi - Nurasila, Nurasila (Program Studi Ilmu Perpustakaan dan Informasi Fakultas Adab dan Humaniora UIN Sulthan Thaha Saifuddin Jambi, 2019)
Introduction. In this study researchers explain about how user’s perceptions about the attitude of librarians in providing services to the UPT UIN STS Jambi circulation service. Whit this research, we can find out how he attitude of librarians in providing service in UPT UIN STS Jambi circulation service is sees from the perpective of visitors. Data Collection Method. The method that researchers use is qualitative research method. Resource persons in this study were determined by several considerations of people who have used library services and know the librarian code of ethics. The method in collecting data researchers used the method of observation, interviews and documentation. Results and Discussions. The result of this study can be concluded that the services provided by librarians in circulation services UPT UIN STS Jambi to library users are not good, because there are still some attitude of librarians in serving librarians who are not in accordance whit the librarian code of ethics.